ISSUES OF DEVELOPMENT OF ONLINE FINANCIAL SERVICES IN UZBEKISTAN - Tashkhodzhaeva Sevara Yarashevna (Journals Park Publishing, 2024)
This article examines the role and significance of digital technology in the development of online financial services, and the different characteristics of digital online financial services in commercial banks compared to traditional services. The relationship between commercial banks and fintech companies in the development of digital online financial services is also analyzed.
Keywords: online financial services, digitalization, digital services, fintech, remote banking, overdraft, bitcoin, blockchain, cryptocurrency, microcredits.